2005
DOI: 10.1152/japplphysiol.00706.2004
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the upper airway does not augment the cardiovascular response to arousal from sleep in humans

Abstract: The cardiovascular response to an arousal from sleep at the termination of an obstructive apnea is more than double that to a spontaneous arousal. We investigated the hypothesis that stimulation of respiratory mechanoreceptors, by inspiring against an occluded airway during an arousal from sleep, augments the accompanying cardiovascular response. Arousals (Ͼ10 s) from stage 2 sleep were induced by a 1-s auditory tone (85 dB) during a concomitant 1-s inspiratory occlusion (O) and without an occlusion [i.e., con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
3
9
0
1
Order By: Relevance
“…Thus the HR response to a spontaneous arousal is a fixed response. This has been demonstrated in adults (7,29,30,40), and importantly, this is also demonstrated in our two groups of children without DS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus the HR response to a spontaneous arousal is a fixed response. This has been demonstrated in adults (7,29,30,40), and importantly, this is also demonstrated in our two groups of children without DS.…”
Section: Discussionsupporting
confidence: 86%
“…Arousal causes large transient increases in HR, BP, and ventilation that are beyond functional requirements (3,40). In the healthy individual, the magnitude of the cardiorespiratory response to arousal from sleep is remarkably consistent and is not altered by chemoreceptor or upper airway mechanoreceptor stimulation (7,29,30). Autonomic blockade studies performed in dogs have shown that arousal from sleep is associated with both acute cardiac sympathetic activation as well as parasympathetic withdrawal (20).…”
mentioning
confidence: 95%
“…The continuous inspiratory resistance measurement for each breath was divided into 10 data points, the middle 8 of which were averaged to provide a single resistance measurement for each breath. 16,[18][19][20] CPAP was titrated in older adults using the online measurement R L , which was matched to values previously obtained in the younger adult group. For the older adults in whom Pes was not measured (n=11), CPAP was titrated to eliminate any flow limitation and upper airways resistance which was inferred from the shape of the inspiratory flow signal.…”
Section: Discussionmentioning
confidence: 99%
“…The study conformed to the standards set by the Declaration of Helsinki and was approved by The Brompton and Harefield Ethics Committee. Data from the 15 young male adults in the current study has been previously published as the control group 16 ; both studies used the same methodology.…”
Section: Subjectsmentioning
confidence: 99%
“…Isolated arousals in the absence of an apnoea are associated with a small and transient increase in blood pressure with a small sympathetic discharge. 19 An arousal associated with apnoea termination results is at least twice the haemodynamic response as a Heart Lung and Circulation Obstructive sleep apnoea, congestive heart failure and cardiovascular disease 2005;14S:S2-S7 result of increased sympathetic tone, vasoconstriction and increased cardiac output. Experiments in dogs have shown that arousal appears to have a direct effect on cardiac sympathetic activity independent from effects of arterial blood gases, lung volume or ventilation.…”
Section: Arousal Responsesmentioning
confidence: 99%